Factors Influencing Anxiety of Healthcare Workers during the Outbreak of 2019 Novel Coronavirus Disease (COVID-19): A Cross-Sectional Study - Mohammad-Rafi Bazrafshan; Hamed Delam; Maasumeh Elahi; Sahar Akbarpoor; Zohreh Faramarzian (Shiraz University of Medical Sciences, 2021)
Background: The mental health of healthcare workers has been a concern during the outbreak of 2019 novel Coronavirus Disease (Covid-19). Therefore, the present study was designed to evaluate the anxiety of the healthcare workers during Covid-19 epidemic and to discover the factors affecting it. Methods:The present study was a cross-sectional descriptive-analytical study. In this study, the anxiety of 124 nurses, operating room staff, midwives and anesthetists working in different wards of Imam Reza Hospital in Lar in 2020 was assessed using the Corona Anxiety Scale Questionnaire. Results: The results showed that most of the samples were female, married, with a bachelor's degree and an average age of 33 years. 53 (42.8%)  participants had mild anxiety and 34 (27.4%) had severe anxiety. Comparison of anxiety levels based on demographic variables of participants in the study showed that there was no significant relationship between anxiety levels with gender, marital status, education level, and field of study (P> 0.05). Conclusion:According to the results of the study and the worsening of the COVID-19 epidemic, there is a need to strengthen the awareness and address the issues related to mental health of healthcare workers.